Base Substitution Patterns in Partial of the Cytochrome C Oxidase Unit I (COI) mtDNA Genes in the Red Junglefowl (Gallus sp.) of North Sulawesi and some Gallus sp. accessions. - Decky Kamagi (Universitas Negeri Manado, 2023)
Partial of the cytochrome C oxidase unit I (COI) mtDNA genes of the red jungle fowl (Gallus sp.) were isolated and sequenced to examine the base substitution pattern compared to several accessions taken from GenBank. Samples were collected from several areas in North Sulawesi in the form of muscle tissue and prepared with 95% alcohol, and stored at temperatures below 500 C. Total DNA was isolated using the innuPREP DNA micro kit with a modified protocol. The target gene amplification used the primers BirdR1 and BirdF1, and the amplicons were sequenced at the Singapore FirstBase laboratory. Target gene sequences have been blasted through the nucleotide blast program provided by the National Center for Biotechnology Information (NCBI)—sequence analysis using MEGA5 and DnaSPv5 software. Target gene sequences were aligned using the Clustal-W program on MEGA5. The amplified target gene sequence length was 490 bp. The blast results showed that the target gene sequence was 98% identical to the COI gene sequence from several Gallus-gallus accessions from GenBank. The results of multiple alignments between the sequences of some of the genes examined showed the presence of polymorphic sites (S). The number of polymorphic sites (S) is 11, while the conserved sequence (C) is 386/397 = 0.977. The number of haplotypes (h) is 5, and the diversity of haplotypes (Hd) is 0.703. The overall genetic distance average was 0.008. The polymorphic sites and base substitution events occurred at sites number 145 (A↔G), 241 (G↔C), 268 (C↔A), 295 (C↔A), 348 (T↔C), 381(A) ↔T), 384 (T↔C), 390 (T↔A), 393 (C↔T), 394 (T↔C) and 395 (C↔T). The substitution pattern at these polymorphic sites consists of substitution transitions and transversions. The ratio of transition substitution and transversion events (Ts/Tv) = 1.4056. The substitution events at these sites are located at the bases in the first and third positions of the codon. Substitution events at these polymorphic sites partially cause the exchange of amino acids. The exchange of amino acids occurs at codons 49, 81, 90, 99 and 130.